Space Design for Thermal Comfort and Energy Efficiency in Summer - Xiaoyu Du (A+BE: Architecture and the Built Environment)
Passive cooling for thermal comfort in summer is a big issue in low-energy building design. An important reason is global warming because global warming increases the number of cooling degree days. In addition, the energy demand of buildings has increased rapidly due to both the improvement of living standards and the globalisation of modern architecture. And finally, cooling a building is especially a challenge in countries where few resources are available. Passive cooling techniques, where solar and heating control systems are applied, largely depend on the design of the urban morphology and the building shape. The first research question is therefore: What is the relationship between spatial configuration, thermal environment and thermal summer comfort of occupants and how to apply spatial configuration as the passive cooling strategy in architectural design?